2020
DOI: 10.3389/fpsyg.2020.02043
|View full text |Cite
|
Sign up to set email alerts
|

Word Meaning Contributes to Free Recall Performance in Supraspan Verbal List-Learning Tests

Abstract: Supraspan verbal list-learning tests, such as the Rey Auditory Verbal Learning Test (RAVLT), are classic neuropsychological tests for assessing verbal memory. In this study, we investigated the impact of the meaning of the words to be learned on three memory stages [short-term recall (STR), learning, and delayed recall (DR)] in a cohort of 447 healthy adults. First, we compared scores obtained from the RAVLT (word condition) to those of an alternative version of this test using phonologically similar but meani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 98 publications
(132 reference statements)
1
10
0
Order By: Relevance
“…The low proportions would be associated with the meaningless words (pseudowords) used in this experiment. In general, the recall performances of real words are better than those of pseudowords [ 39 ]. Additionally, the participants in this study only learned the pseudowords once in learning tasks.…”
Section: Discussionmentioning
confidence: 99%
“…The low proportions would be associated with the meaningless words (pseudowords) used in this experiment. In general, the recall performances of real words are better than those of pseudowords [ 39 ]. Additionally, the participants in this study only learned the pseudowords once in learning tasks.…”
Section: Discussionmentioning
confidence: 99%
“…VLT completion induces the use of association mnemonics based either on semantic or temporal (i.e., serial order) clustering (Cremona et al, 2020; Gross & Rebok, 2011; Worthen & Hunt, 2017). Here, we showed that the use of association‐based mnemonics mediated the VLT–CA1 volume relationship, revealing that the best VLT performers used association‐based mnemonics that positively correlated with CA1 volume.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, to explore whether an association‐based hippocampal computation explains the VLT–HsVol relationship, we collected mnemonics reported by the participants to retain the list of words in Sample 1. The method is detailed in Cremona et al (2020). In short, 377 participants reported association‐based mnemonics, grouping words from either their meaning (semantic clustering) or position in the list (temporal clustering).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations